Solid Waste Management of Chicken Farming in Besuki Village, Ampel Sub-District, Boyolali Regency: An Effort Toward Cleaner Production in Broiler Chicken Farming Business - Bayu Setiawan; Hosiana Albertin Angu Bima; Debi Debora Okowali; Chelsea Jaclynn Husig; Widhi Handayani (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
Broiler farming is one of businesses that can be developed to meet the needs of animal-based protein for the community, in addition to providing jobs and increasing people's income. However, broiler farms release chicken manure whose smell can disturb the surrounding community. This study was conducted to explain the management of chicken farm waste that has been running and to analyze the advantages of processing chicken manure into compost as an effort to realize the clean production of broiler farms in Besuki village, Ampel sub-district, Central Java province. This research was conducted at CV Utomo Farm, Besuki Village, Ampel District, Central Java. A qualitative method with primary and secondary data was used. Primary data were collected by interview and observation, while the secondary data was collected from literatures. The data was analyzed by qualitative analysis. If the chicken manure is processed into compost, it is estimated that 10.319 tons of compost will be produced which will provide an additional income of Rp. 20,630,000.00, and the profit will reach Rp. 13,728,625.00 on a production scale of 27,000 chickens per 35 days. This effort will apply the clean production to minimize pollution by maximizing output.